In vitro antioxidant potential of linolenyl alcohol isolated from Cayratia trifolia L. (International Journal of Pharmaceutical Sciences and Drug Research, 2024)
Cayratia trifolia, a plant rich in bioactive compounds, has been known for its diverse pharmacological properties, including antioxidant activity. In this study, we focus on linolenyl alcohol, a compound isolated from Cayratia trifolia, and investigate its antioxidant potential through in vitro analysis. Linolenyl alcohol was extracted from Cayratia trifolia leaves using standard extraction techniques and characterized using spectroscopic methods. The antioxidant activity of linolenyl alcohol was evaluated using well-established antioxidant assays. The results explored significant antioxidant activity of linolenyl alcohol, with dose-dependent scavenging of free radicals observed in all assays. Overall, our findings highlight the antioxidant potential of linolenyl alcohol from Cayratia trifolia, suggesting its utility as a natural antioxidant agent in pharmaceutical and nutraceutical applications. Further investigations are warranted to explore its therapeutic benefits and potential clinical applications.